2013
DOI: 10.1136/acupmed-2012-010206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acupuncture for Cancer Symptoms in a Cancer Institute in Brazil

Abstract: Introduction Acupuncture has been progressively included in the practice of mainstream medicine in recent decades. The State of Sao Paulo Cancer Institute is a public hospital established in 2008 and its acupuncture service follows the experience and model of several oncology centres in the USA, aiming to optimise the treatment of symptoms such as postoperative pain, oncological pain, neuropathic pain, nausea, vomiting, xerostomia and fatigue induced by chemotherapy. This paper describes the population given a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In Chile, the Clinica Alemana, the Arturo Lopez Perez Foundation, the National Cancer Institute, and the Calvo Mackenna Hospital also offer TCIM services integrated with Western conventional therapies to patients with cancer 64,65 . Several Brazilian medical centers have established integrative oncology programs with an academic focus on clinical care, teaching, and research: Hospital Israelita Albert Einstein in Sao Paulo and the Brazilian NCI‐Designated Cancer Centers (the National Cancer Institute in Rio de Janeiro and the university hospitals of Sao Paulo and Fortaleza) 66‐70 . Brazil has a national policy that integrates TCIM within the United Health System, which now includes 29 practices 71‐73 .…”
Section: Examples Of Progress and Challenges Of Integrating Tcim And ...mentioning
confidence: 99%
“…In Chile, the Clinica Alemana, the Arturo Lopez Perez Foundation, the National Cancer Institute, and the Calvo Mackenna Hospital also offer TCIM services integrated with Western conventional therapies to patients with cancer 64,65 . Several Brazilian medical centers have established integrative oncology programs with an academic focus on clinical care, teaching, and research: Hospital Israelita Albert Einstein in Sao Paulo and the Brazilian NCI‐Designated Cancer Centers (the National Cancer Institute in Rio de Janeiro and the university hospitals of Sao Paulo and Fortaleza) 66‐70 . Brazil has a national policy that integrates TCIM within the United Health System, which now includes 29 practices 71‐73 .…”
Section: Examples Of Progress and Challenges Of Integrating Tcim And ...mentioning
confidence: 99%
“…Whether the herbal substance induced the metabolism of axitinib via CYP3A4 or whether another unidentified interaction took place, can, however, not be deduced from this case report. In an in vitro study, Dang-gui and Bai zhu have been identified as CYP3A4-inducers [6]. It is, however, not reported whether and to which extent the other herbal compounds of the mixture exert effects on drug metabolism, so that their contribution to the effect remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, adjuvant therapy with 5 mg axitinib orally twice daily and pembrolizumab 200 mg intravenously every 3 weeks was started [1]. A few weeks after the initiation of systemic treatment, the patient mentioned that she was exploring oncology acupuncture because of gastrointestinal side effects related to previous surgery [6]. She also reported mild redness, swelling, and sometimes pain in her hands and feet, possible symptoms of the hand-foot syndrome recognized as a common side effect of the TKI axitinib [7].…”
Section: Case Presentationmentioning
confidence: 99%